Wound Healing Complications Following Guided Bone Regeneration for Ridge Augmentation: A Systematic Review and Meta-Analysis - Lim, Glendale; Lin, Guo-Hao; Monje, Alberto; Chan, Hsun-Liang; Wang, Hom-Lay (The International journal of oral and maxillofacial implants, 2018)
The rate of developing soft tissue complications that accompany guided bone regeneration (GBR) procedures varies widely, from 0% to 45%. The present review was conducted to investigate the rate for resorbable versus nonresorbable membranes and the timing of soft tissue complications. Electronic and manual literature searches were conducted by two independent reviewers using several databases, including MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Cochrane Oral Health Group Trials Register, for articles published through July 2015, with no language restriction. Articles were included if they were clinical trials aimed at demonstrating the incidence of soft tissue complications following GBR procedures. Overall, 21 and 15 articles were included in the qualitative and quantitative synthesis, respectively. The weighted complication rate of the overall soft tissue complications, including membrane exposure, soft tissue dehiscence, and acute infection/abscess, into the calculation was 16.8% (95% CI = 10.6% to 25.4%). When considering the complication rate based on membrane type used, resorbable membrane was associated with a weighted complication rate of 18.3% (95% CI: 10.4% to 30.4%) and nonresorbable membrane with a rate of 17.6% (95% CI: 10.0% to 29.3%). Moreover, soft tissue lesions were reported as early as 1 week and as late as 6 months based on the included studies. Soft tissue complications after GBR are common (16.8%). Membrane type did not appear to significantly affect the complication rate, based on the limited number of data retrieved in this study. Technique sensitivity (ie, soft tissue management) may still be regarded as the main component to avoid soft tissue complications and, hence, to influence the success of bone regenerative therapy.